Involucrin synthesis and tissue assembly by keratinocytes in natural and cultured human epithelia (The Rockefeller University Press, 1981)
Different stratified squamous epithelia, whether they bear a stratum corneum or not, are shown by immunofluorescence to possess the precursor protein of the cross-linked envelope that is characteristic of epidermal s. corneum. This protein, involucrin, is not present in the deepest epithelial cells but appears in the course of their outward migration. The boundary at which involucrin first appears can sometimes by correlated with a visible boundary between zones of large and small cells. Cultured keratinocytes, derived from all stratified squamous epithelia (epidermal, corneal, conjuctival, esophageal, lingual, and vaginal), form colonies that grow together to form a stratified epithelium. The cells of the basal layer are nearly always free of detectable involucrin, but, in contrast to the natural epithelium, this protein usually makes its appearance in the cells immediately above the basal layer. When a cultured epithelium derived from epidermal keratinocytes is detached and applied as a graft to animals, the cells flatten and the distinctness of the basal layer is at first reduced; but with time the organization of the epithelium becomes more characteristic of epidermis. Cell size and shape become more orderly along the cell migration pathway, and involucrin first appears at some distance from the basal layer, instead of in immediately suprabasal cells, as in the cultured epithelium. The progeny of dissociated and cultured keratinocytes are therefore able, when grafted, to reassemble an epidermis in which the timing of specific gene expression is restored to that of the original tissue.